KONSEP PENDIDIKAN KELUARGA DALAM PERSPEKTIF ISLAM - Ubabuddin Ubabuddin (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2018)
The first and the most important children education in Islam is the family education with Islamic perspective.Family Education with Islamic perspective is education based on the guidance of Islam which is applied in the family intended to forming children to be a peoples who faithful and cautious to God Almighty, and has noble character that includes ethics, moral, character, spiritual or understanding and experience in religious values in everyday life. This is one form of amar makruf nahi munkar in family life by providing education to children based on the teachings of Islam. Children in their growth require a variety of processes educated by the father and mother in the family environment. Pattern or method of religious education in Islam is basically modeled on the behavior of Prophet Muhammad in his family and his friends,because everything that is done by Prophet Muhammad is the manifestation of Qur’an’s content.